Urgency of Digital Technology in Increasing The Professionalism of Prospective Arabic Language Teachers in Teaching Assistance Activities - Yanti, Elly Rahmah; Muflihah, Muflihah (Tanfidziya: Journal of Arabic Education, 2024)
This article discusses research about urgency of digital technology in increasing the professionalism of prospective Arabic teachers in teaching assistance activities. In this digital era, Arabic language learning will decline if it is not balanced by improving the quality of teachers by using digital technology in learning. This research focuses on practical experience of prospective teachers in applying technology during the teaching process in teaching assistance activities. This research uses a qualitative approach method with a case study method. Digital technology has a very important role in learning Arabic because using digital technology brings many benefits to teachers and students. There are very few drawbacks to using digital technology in learning Arabic so it is appropriate to use digital technology during learning. The existing deficiencies become an evaluation for teachers to be able to minimize them and find solutions to overcome them.